PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PROGRAM AIR ISI ULANG DI GAMPONG ULEE MADON KECAMATAN MUARA BATU KABUPATEN ACEH UTARA - Hayatun Nufus (Jurnal Syariah dan Ekonomi Islam, 2024)
Economic empowerment can be realized if the core targets can focus on alleviating poverty, creating jobs, improving people's welfare. Therefore, the authors are interested in researching Community Economic Empowerment through the Water Refill Program in Ulee Madon Village, Muara Batu District, North Aceh Regency with the formulation of the problem that the author sets, namely: How is community economic empowerment through refill water programs in Ulee Madon Village, Muara District Batu, North Aceh Regency and What are the Inhibiting and Supporting Factors for community economic empowerment through the refill water program in Ulee Madon Village, Muara Batu District, North Aceh Regency. The research benefits include practical and theoretical benefits. The research method used is descriptive qualitative and phenomenological approach. The results showed that community economic empowerment through the refill water program in Ulee Madon Village, Muara Batu District, North Aceh Regency contained several activities such as programs, mentoring.